ANALISIS KONTRIBUSI PENDAPATAN PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH KOTA BANJARMASIN - Irfan Yamin; Mellani Yuliastina; Fatimah Fatimah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
The primary objective of this research is to examine the role that parking taxes play in the Regional Original Revenue of Banjarmasin City. From 2019 to 2023, this research used data from Banjarmasin City's parking tax revenue realizations and Regional Original Revenue. Descriptive data analysis is the method used for analyzing the data. According to the study's findings, the variable of parking tax income is positively and significantly related to Regional Original income Banjarmasin City. The increase in the Regional Original income Banjarmasin City is directly proportional to the increase in the parking tax income. Throughout the study period, parking taxes contributed an average of 1,91% of Regional Original Revenue in Banjarmasin City.